2020
DOI: 10.31000/prima.v4i1.2032
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran Untuk Meningkatan Kemampuan Berpikir Kreatif

Abstract: Tujuan penelitian ini adalah mengembangkan perangkat pembelajaran (RPS dan RPP) yang berkualitas dari aspek kevalidan, kepraktisan, dan efektif untuk meningkatkan kemampuan berpikir kreatif sebagai upaya menuju era industry 4.0. Penelitian ini termasuk dalam penelitian pengembangan. Rancangan penelitian ini terdiri dari 10 langkah, yaitu: (1) penelitian terhadap produk penelitian yang sudah ada, (2) studi literature, (3) perancangan dan pembuatan instrumen penelitian, (4) perancangan pengembangan produk, (5) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
1
3
0
2
Order By: Relevance
“…According to Irwanto (1994), student perception describes the knowledge they have about the object they perceive. Thus, this research confirms that students' positive perceptions about creative thinking have shown their ability to think divergently such as fluency, where students are able to provide various thoughts about things they do not yet understand (Malik, Agustina & Wardhany, 2019); flexibility, where students are able to provide several alternative ideas or thoughts in solving problems (Vally et al, 2019); originality, where students are able to find unusual ideas, different thoughts that are rarely given by other people (Arvianto & Ardhana, 2020); elaboration, where students are able to detail various ideas or expand the ideas produced (Sugiyanto et al, 2018). In this way, biology education students at the Mandalika University of Education will be able to become prospective science teachers who think modernly and are flexible to face educational challenges in the 21st century (Himmah, Handayanto & Kusairi, 2021).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…According to Irwanto (1994), student perception describes the knowledge they have about the object they perceive. Thus, this research confirms that students' positive perceptions about creative thinking have shown their ability to think divergently such as fluency, where students are able to provide various thoughts about things they do not yet understand (Malik, Agustina & Wardhany, 2019); flexibility, where students are able to provide several alternative ideas or thoughts in solving problems (Vally et al, 2019); originality, where students are able to find unusual ideas, different thoughts that are rarely given by other people (Arvianto & Ardhana, 2020); elaboration, where students are able to detail various ideas or expand the ideas produced (Sugiyanto et al, 2018). In this way, biology education students at the Mandalika University of Education will be able to become prospective science teachers who think modernly and are flexible to face educational challenges in the 21st century (Himmah, Handayanto & Kusairi, 2021).…”
Section: Resultssupporting
confidence: 71%
“…One of the main competencies in creative thinking is divergent products, including fluency, flexibility, originality and elaboration (Torrance, 1998). These four indicators are important because with the ability to think fluently, students will be able to provide various thoughts about things they do not yet understand (Malik, Agustina & Wardhany, 2019), flexible thinking will help students provide several alternative ideas or thoughts in solving problems (Vally et al, 2019), students can use original thinking to find unusual ideas, thoughts that are different and rarely given by other people (Arvianto & Ardhana, 2020), and elaborative thinking skills will be able to detail various ideas or expand the ideas produced (Sugiyanto et al, 2018). Based on the description of indicators of creative thinking abilities, it is hoped that students will be able to become mentally flexible modern humans to survive and compete in facing challenges in the 21st century (Himmah, Handayanto & Kusairi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of teaching materials in learning that has been going on so far is to teach students according to the textbooks used by lecturers (Nurmita, 2017). Several studies related to the development of teaching materials and learning tools have been carried out and have been proven to be effective in improving students' creative thinking ability (Sari & Wulanda, 2019) (Fadhilaturrahmi, Ananda, & Yolanda, 2021) (Salamiyah & Kholiq, 2020) (Arvianto & Ardhana, 2020).…”
Section: Thinking Evaluationmentioning
confidence: 99%
“…exists at the moment. According to (Arvianto & Ardhana, 2020) the learning process is not optimal due to 2 (two) things, namely: (a) the informative learning process, which has not been directed towards an active process for learners to build their own knowledge; (b) the learning process is learnercentred, not yet directed towards learner-centred learning. Learning management includes productivity, democratization, cooperation, effectiveness and efficiency, as well as directing the vision, mission and goals set, especially in the field of entrepreneurship which is a current problem.…”
Section: Introductionmentioning
confidence: 99%